Review of recent innovations in portable child growth measurement devices for use in low- and middle-income countries. (17th November 2021) - Neale, Geoffrey; Gaihre, Santosh; O'Gorman, Pearse; Price, Ruth K.; Balzategi, Ane Galdos; Barrientos, Catalina Herrera; Rawal, Shweta; Morgan, Margaret; McNulty, Helene
Abstract: Improving nutritional status is fundamental to addressing challenges in child health in low- and middle-income countries (LMICs) and a priority for international organisations such as the United Nations Children's Fund (UNICEF) and the World Health Organisation (WHO). Despite the global consensus that child growth is a key indicator of child nutrition and health, the development of low-cost, accurate and child-friendly growth measurement devices that are fit for purpose in LMICs remains elusive. Recognising these limitations, UNICEF recently published a Target Product Profile (TPP) calling for the development of new state-of-the-art height and length measurement devices. The purpose of this review was to examine current growth measurement devices in relation to this UNICEF TPP requirement and set the stage for the development of new devices. The findings show that there is a gap in the product market for accurate portable length and height measurement devices. In particular, our review indicates that devices in current use generally lack capabilities for automated data recording and transfer of data to a central database, and are often not child-friendly. We conclude that future innovations in length and height measurement devices should focus on addressing these issues.